2009
DOI: 10.1021/ed086p514
|View full text |Cite
|
Sign up to set email alerts
|

The Adverse Effects of Le Châtelier's Principle on Teacher Understanding of Chemical Equilibrium

Abstract: Chemistry education researchers have noted the inadequacy of Le Châtelier's principle (LCP) for decades (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). They have shown how apparently reasonable applications of LCP can result in incorrect predictions about the effects of changes in concentration, volume, pressure, or temperature on chemical systems at equilibrium. Because LCP has no value for chemistry teachers and students other than historical interest, some researchers (13-19) have criticized the over-emphasis of L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 14 publications
1
44
0
5
Order By: Relevance
“…By the analysis given above, it can be concluded that Le Chatelier's principle cannot be applied in the example represented by Eq. 1, since the concentrations for both N 2 and H 2 are affected by the addition [5]. When 1 mole of N 2 is added x N 2 is increased by 0.5-0.6973 from rows No.…”
Section: Limitations Of the Le Chatelier's Principle Demonstrated By mentioning
confidence: 99%
See 3 more Smart Citations
“…By the analysis given above, it can be concluded that Le Chatelier's principle cannot be applied in the example represented by Eq. 1, since the concentrations for both N 2 and H 2 are affected by the addition [5]. When 1 mole of N 2 is added x N 2 is increased by 0.5-0.6973 from rows No.…”
Section: Limitations Of the Le Chatelier's Principle Demonstrated By mentioning
confidence: 99%
“…It is more useful to obtain a general understanding with theoretical analysis. A simple analysis [5] shows that the addition of N 2 at constant T and P will produce more N 2 because of the dilution of H 2 resulting from the addition. But it will be clear that this explanation does not help much in developing a more systematic mathematical method [15][16][17].…”
Section: Background Informationmentioning
confidence: 99%
See 2 more Smart Citations
“…Os dados mostram uma grande quantidade de conceitos alternativos provenientes do ensino médio (Akkus et al, 2003), cuja origem pode ser atribuída, pelo menos em parte, aos próprios professores que carregam consigo conceitos alternativos sobre equilíbrio químico ) e sua natureza fenomenológica -notavelmente uma associação inconsistente com o princípio de Le Chatelier (Cheung, 2009). Além disso, há dados sobre os conceitos alternativos em EQ dentro do enfoque dos diferentes níveis de representação (Carobin, Serrano, 2007), que será abordado adiante.…”
Section: Introductionunclassified